Principles and laws of teaching as an important basis for ensuring the effectiveness of education - Choriyev Islom Normo’minovich (Zien Journals, 2022)
The article deals with the principle of regularity and consistency in the acquisition of knowledge, the importance of the principle of scientific and comprehensible teaching material, the role of the principle of linking theory with practice in teaching, increasing the awareness and creative activity of students in the learning process. are illuminated.
Keywords: didactics; principles; regularity; consistency